Andean Cosmovision in «El niño del carrizo» by César Vallejo - Villafán Broncano, Macedonio (2019)
«El niño del carrizo» by Vallejo narrates the quest of a reed that the young Miguel partakes when trying to decorate the bust of a religious statue during the Holy Week. This quest is embedded in the Andean cultural matrix, and the story explores the traversing of Miguel from a Western cosmovision to an Andean one. This crossing from one cosmovision to the other leads to the cultural finding of the character. Miguel’s perception is linked to cultural references, those of the landscape in which the story is inscribed to, such as Santiago de Chuco, where the Andean culture is manifested in its culli version, which Vallejo captures in depth. The episodic moments that Miguel shares with his plants, dogs, and the ecstatic moment when Miguel drinks water, characterize a conscious Andean gleam typical of Vallejo’s works. Water, for instance, acquires relevance since it is the medium that connects men with nature— with the Mother Earth. This paper approach is cultural; another useful methodology was to trace Santiago de Chuco’s oral tradition.